Patients with Blepharitis Are at Elevated Risk of Anxiety and Depression - Chiang, Chun-Chi (Public Library of Science, 2013)
PURPOSE: Population-based cohort study on the risk of anxiety and depression in patients with blepharitis is limited. This study evaluated whether blepharitis patients are at a higher risk of anxiety and depression. DESIGN: A retrospective cohort study. METHODS: We used the universal insurance claims data from 1997 to 2010 in Taiwan to identify annually patients with newly diagnosed blepharitis (N = 9764) and without the disease (N = 39056). Incidences, rate ratios (IRR) and hazard ratios (HR) of anxiety and depression were measured for both cohorts by baseline demographic characteristics and comorbidities until the end of 2010. RESULTS: Compared with the non-blepharitis cohort, the blepharitis cohort had higher incidence of anxiety (15.9 vs. 9.5 per 1000 person-years), with an adjusted HR of 1.58 (95% confidence interval (CI) = 1.46–1.70). The incidence of depression was also higher in the blepharitis cohort (7.66 vs. 5.05 per 1000 person-years), with an adjusted HR of 1.42 (95% CI = 1.28–1.58). The blepharitis cohort to the non-blepharitis cohort IRR decreased from 1.73 in the first quartile to 1.32 in the 4(th) quartile for anxiety, and from 1.67 to 1.29 for depression. CONCLUSIONS: Patients with blepharitis are at elevated risks of anxiety and depression. The risk is higher in earlier period after the diagnosis of blepharitis, and declines by time, but remains significantly higher for those with blepharitis than those without blepharitis.